A Comprehensive Treatment Strategy for Chronic Periodontitis Based on Disease Stage and Individual Patient Characteristics - Xikmatuloyevna, Marupova Madina (American Journal of Biomedicine and Pharmacy, 2026)
Chronic periodontitis represents a progressive inflammatory condition of the supporting structures of the teeth that may lead to significant functional impairment and loss of dentition if inadequately managed. Its clinical course varies widely depending on individual patient factors, including systemic health status, genetic predisposition, lifestyle habits, and disease stage. This study explores a comprehensive treatment approach for chronic periodontitis that integrates patient-specific characteristics with the severity of periodontal involvement to optimize clinical outcomes. The findings demonstrate that targeted interventions, including mechanical debridement, pharmacological support, behavioral counseling, and ongoing maintenance, result in measurable improvements in periodontal stability, reduction of probing depth, attachment gain, and patient-reported satisfaction. The approach highlights the necessity of individualized periodontal care strategies for effective disease management and long-term oral health preservation. Chronic periodontitis is a multifactorial inflammatory disease that affects the supporting tissues of teeth, often resulting in progressive bone loss, tooth mobility, and functional impairment if not properly addressed. The management of chronic periodontitis requires a comprehensive approach that considers the patient’s individual characteristics, systemic health, and the severity of periodontal destruction. This study examines a structured treatment strategy tailored to both disease stage and patient-specific factors, integrating mechanical debridement, pharmacological support, and behavioral interventions. The clinical outcomes demonstrate notable improvements in periodontal stability, reduction of probing depths, gain in clinical attachment levels, and enhanced patient-reported quality of life. Personalized therapy also facilitates better adherence to oral hygiene practices and long-term maintenance, underscoring the importance of individualized care plans in contemporary periodontal management. The findings highlight the critical role of comprehensive, patient-centered approaches in mitigating disease progression and promoting oral health sustainability.